Implementasi kebijakan pembelajaran daring pada masa pandemi covid19: Studi pada SMP Negeri 1 Kubu Babussalam Kabupaten Rokan Hilir - Tamrin Tamrin; Suhartini Suhartini (STIE Bangkinang Publishing, 2023)
Online learning is learning that uses the internet for accessibility, connectivity, flexibility, and the ability to bring up various types of learning interactions. The purpose of this study is to describe the implementation of online learning policies and the supporting and inhibiting factors of the online learning process. This study used the descriptive qualitative method. The data used are primary and secondary data obtained using observation, interviews, and documentation. Methods of data analysis carried out by qualitative methods. The results of this study concluded that the implementation of online learning at SMPN 1 Kubu Babussalam was going well, This was based on all students being able to take part in the online learning model, which was carried out through WhatsApp media, and there were quite satisfactory results from the grades obtained by the students. Factors supporting the implementation of online learning at SMPN 1 Kubu Babussalam are the quality of human resources, in this case, the teachers are good. Teachers have good abilities and competencies in their respective fields, which are very supportive and influence the results of learning activities. The inhibiting factor for the implementation of online learning is the weak internet network when the learning process is carried out. For students who are in areas where signal coverage is rather difficult to obtain, it is clearly an obstacle to participating in learning